PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DALAM MATERI UNSUR - UNSUR INTRINSIK TERHADAP NASKAH DRAMA PADA SISWA KELAS XI PH5 DI SMK NEGERI 1 NUSA PENIDA TAHUN PELAJARAN 2023/2024 - Erawan, Dewa Gede Bambang; Sutantri, Ni Wayan Nopi; Lastra, I Kadek (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2024)
This study aims to improve student learning outcomes by applying PjBL (Project based Learning) to the material of intrinsic elements of drama. This research is a type of classroom action research (PTK). This research consists of two cycles where there are three meetings in each cycle. Each cycle consists of planning, action, observation, and reflection. The subjects of this study were students of class XI PH 5 SMK Negeri 1 Nusa Penida with a total of 20 students. Data sources were obtained from teachers and students through observation and evaluation tests. The data analysis technique used qualitative descriptive and quantitative descriptive analysis. The results showed an increase in student learning outcomes as indicated by the increasing number of students who reached KKM (complete) from pre-action to cycle II. Pre-action learning completeness was 40%, cycle I 55.00%, and cycle II 100.00%. In addition, it is also supported by an increase in student learning abilities. This class action research with the PjBL model can be said to be successful and effective in applying to Indonesian language learning on the material of intrinsic elements of drama because it can achieve the predetermined success indicators, namely more than 75% of students' scores reach the KKM. Based on the findings of the research results, it can be concluded that the learning outcomes of students in class XI PH 5 can improve after using the project based learning model.